Kepastian Hukum Kewenangan Nazhir: Ruislag Tanah Wakaf Untuk Kepentingan Bisnis - Sefli Suharman; Fauzie Yusuf Hasibuan (Postgraduate of Jayabaya University, 2016)
Regulation Legislation Endowments to property that is already in endowments is prohibited to do exchange (ruislag), excluded when ruislag used for public interest in accordance with the general plan spatial layout under the provisions of the legislation applicable and does not conflict with sharia. This research is descriptive research analysis using normative juridical approach, the research literature that focuses on secondary data by conducting a study or a thorough analysis and depth to the entire of secondary data adapted to the problem in this research. The results showed that to exchange (ruislag) of waqf land for business is one from the other forms of legal interest in doing ruislag for waqf property which is not stipulated in the regulations of endowments. Based on the decision of Judicial Review (PK) The Supreme Court No. 27 PK / AG / 2008 Nazhir convicted for committing an unlawful act on the land of endowments that is ruislag for the benefit of textile business. Should be Nazhir in doing ruislag to property that is already in endowments guided by the procedures and requirements set forth in Regulation Legislation Endowments applicable especially Article 41 in Act No. 41 of 2004 on endowments set ruislag only in the public interest.